Salient Factors Affecting The Reputation Of Real Estate Agency Migration In China - Li, Fengzhu; Wareewanich, Thitinant (Migration Letters, 2024)
In the era of social media, the management of real estate reputation encounters formidable challenges. The research aimed to identify and analyze the correlations between factors such as Repeated exposure, Online review, CEO reputation, Welfare of employees, Quality of service, Innovation ability, and social responsibility, and their impact on real estate agency reputation. A non-probability judgment sampling method was employed, focusing on middle and senior-level personnel in real estate companies and consumers in Beijing using Douyin. The sample consisted of 506 valid responses. Data analysis was conducted using statistical tools to compute reliability, validity, confirmatory factor analysis, path analysis, along with the Bootstrapping algorithm for testing mediating effects, hence, to construct a structural equation model. The results revealed that all these variables positively correlated with real estate agency reputation. The study concludes that digital engagement and organizational characteristics significantly influence consumer perceptions in the real estate sector. These findings provide valuable insights for real estate agencies, platform developers, and policymakers, highlighting the importance of a multifaceted approach in the digital real estate market. This research contributes to the academic literature by integrating traditional theories with digital platform dynamics, offering a novel perspective on consumer behavior in the digital age. However, limitations such as the sampling method and platform-specific focus suggest the need for broader future research.